Combination of AWE (criterion) feedback with the process approach and its impact on EFL writing content/idea development and organization - Algburi, Entesar; Razali, Abu Bakar; Nimehchisalem, Vahid; Ismail, Lilliati (Human Resources Management Academic Research Society (HRMARS), 2024)
While being very important and useful, in certain English as a foreign language (EFL) setting the act of providing feedback on writing constructs considered to be time-consuming that can lack meaning and focus, especially if not done well. In this regard, the development and use of automated writing evaluation (AWE) software is anticipated to assist EFL learners to improve writing skills through feedback as well as helping teachers by saving time and effort and supporting their writing instruction. This paper examines the influence of automated feedback (through the use of Criterion) with the process approach on the improvement of EFL learners’ writing performance specifically in relation to content/idea development and organization. The study employed a quasi-experimental research design with pre- and post-tests as well as the intervention which is the exposure to and use of automated writing evaluation (AWE) software with the process approach. Twenty-six Iraqi third year undergraduate students from the College of Education for Women at Baghdad University were assigned to receive automated feedback on their essays from the Criterion online writing evaluation system. Another 26 undergraduate students were assigned as a control group that received feedback from their writing instructor on their essays regarding content/idea development traditionally. According to the findings of the study, the incorporation of AWE software with process approach has a significant impact on students’ academic writing in term of improve content/idea development and organization. The experimental group outperformed the control group in their post-test results. This suggests that incorporating of process approach with AWE software was valuable in improving writing skills in term of content and organization. Each step of cognitive writing processes had overcome the barriers experienced by Iraqi EFL learners. They (Iraqi EFL learners) benefitted from Criterion features of planning ideas to develop essay content and reorganize them effectively. This suggested that incorporating automated feedback with process approach have great benefit in fostering academic writing improvement. Some pedagogical implications were highlighted.